THE EFFECT OF ATI (APTITUDE TREATMENT INTERACTION) LEARNING MODEL TO ACTIVITIES AND STUDENTS PHYSICS SCIENCE GENERIC - Zulkipli Dongoran (Jurnal Pendidikan Fisika, 2014)
This study aims to analyze: (1) the difference between the model of learning activities of students immediately ATI learning model, (2) differences in physical science students' generic capabilities between direct instructional model and learning model ATI. This study was a quasiexperimental study. The population was SMA Negeri 11 students. The sample selection is done at random to randomize the class. The instrument used consisted of: (1) observation sheet learning activity (2) tests the ability of generic science subject matter physics with dynamic power. The test is used to obtain the data is in the form essays. The data in this study were analyzed using a comparative analysis of two independent samples. The results showed that: (1) activity taught students with learning model ATI better than students who are taught using a direct instructional model (2) the ability of generic science physics students taught using learning model ATI better than students who are taught using direct instructional model.